THU0147 Treatment response in antidepressants-treated ra patients with depressive and anxiety disorders receiving dmards and biologics on a five-year follow-up. (12th June 2018) - Abramkin, A.; Lisitsyna, T.; Veltishchev, D.; Seravina, O.; Kovalevskaya, O.; Nasonov, E.
Abstract : Background: Anxiety and depressive disorders (ADD) significantly affect disease activity and prognosis, treatment compliance and response in rheumatoid arthritis (RA) patients (pts). Personalised antidepressant treatment of ADD could be beneficial in managing of RA in this group of patients. Objectives: To compare treatment response and remission rates in 4 groups of RA patients with ADD treated with DMARDs, biologics and antidepressants at the endpoint of a prospective 5 years study. Methods: 128 RA-pts were enrolled in pilot study. All of them met the full ACR criteria for RA classification. 86% RA-pts were women with a mean age of 47, 4±1, 0 (M±m) yrs. RA activity was evaluated with DAS28 and SDAI, remission was defined according to DAS28 (≤2, 6) and ACR/ EULAR 2011 (SDAI ≤3, 3) remission criteria, response to treatment was classified according to EULAR and ACR/ EULAR 2011 (SDAI) response criteria. Average DAS28 and SDAI scores at baseline were high and moderate (5, 25±0, 16 and 33, 5±1, 38 (M±m)). 62, 6% RA-pts were taking prednisone (9 (5; 10) mg/day (Me (25%; 75%)), 75, 1% - DMARDs, 32% - biologics (rituximab – 12, 5%, anti-TNF-α – 11%, anti-IL6 – 6, 2%). ADD were diagnosed in 123 (96, 1%) of RA-pts by psychiatrist in accordance with ICD-10 in semi-structured interview. Severity of anxiety and depression was evaluated with Montgomery–Asberg Depression Rating Scale (MADRS) and Hamilton Anxiety Rating Scale (HAMA). RA-pts with ADD were divided into the following treatment groups: 1 – DMARDS (n=39), 2 - DMARDs+antidepressants (sertraline or mianserine) (n=43), 3 – DMARDs+biologics (n=32), 4 - DMARDs+biologics+ antidepressants (sertraline or mianserine) (n=9). Biologics treatment duration varied from 1 to 6 years, antidepressants – from 6 to 96 weeks. Differences in baseline disease activity scores were significant only in DAS28 for group 1 versus group 4 (4, 95±0, 24 vs 6, 45±0, 52; p=0, 026). Results: The RA-treatment efficacy was evaluated at 5 years endpoint in 83 RA-pts. The percentage of patients who achieved good response according to EULAR (DAS28) criteria was higher (p<0, 05) in groups 2 (41, 4%) and 3 (28, 6%) vs DMARDs (4, 2%) group. In biologics groups (3 and 4) good response according to SDAI criteria was more (p<0, 05) prevalent (52, 4% and 88, 8% respectively) than in group 2 (25%), and vice versa for moderate response. In addition, patients in biologics groups achieved good response significantly more often than moderate (p<0, 05). EULAR and SDAI nonresponse rates were significantly lower in 2–4 vs DMARDs groups. Patients treated with DMARDs+antidepressants achieved remission significantly more often (p=0, 024) than ones receiving DMARDs only. Remission by ACR/ EULAR 2011 criteria was reached exclusively by DMARDs+antidepressants patients. Conclusions: our findings demonstrate that successful treatment of ADD with antidepressants provides more significant positive influence on treatment response to DMARDs and biologics in rheumatoid arthritis patients on a five-year follow-up. Diagnosis and treatment of ADD would potentially play an important role in individualised management of RA patients Disclosure of Interest: None declared